The Balance of Personality - Allen, Chris (Open textbook library., 2020)
This open access textbook was developed as an upper division undergraduate textbook for theories of personality. Its intended audience are students from Portland State University enrolled in Psychology 432 Personality course. The chapters are shorter than some personality textbooks and in this particular course Psy 432 the textbook is combined with other readings including scientific articles on personality. This open access textbook may be of interest to other courses interested in teaching about theory and research on personality.